Bund and Boundary Plantation: A Prominent Feature of Indian Agroforestry - P A, Clara Manasa; Salimath, Supriya K; Hedge, Ramakrishna; Gooli, Manjunath (Indian Journal of Agroforestry, 2022)
Mission on Agroforestry under National Mission for Sustainable Agriculture  “Har Medh Par Pedh” - tree planting with agricultural crops is gaining importance in the recent days. The advantages of integrating trees into agricultural farms had been recognized  and owing to this prospect, bunds and boundary plantations are encouraged under agroforestry practice. The large areas available on bunds, river banks and canal banks provide a great scope and opportunity for the tree planting and have proven to benefit the farmers in bith economic and ecological ways. Multipurpose tree species with short, medium, and long-term returns can be planted so that farmers may get additional income at regular intervals. However, a comprehensive information on the importance, scope and management guidelines is still lacking. This review includes the importance, scope of bund and boundary plantation in farmland, suitable species to be recommended for different areas, and guidelines and management followed for tree planting.